Canone inverso. L’eredità liberal-progressista di Émile Durkheim - Pendenza, Massimo (SocietàMutamentoPolitica, 2017)
Durkheim has historically long been associated with conservative thought and the defense of social order. Our paper on the contrary explores three separate paths of research which, we consider have more than others, over the last twenty years, been of fundamental relevance if not revolutionary, in revisiting Durkheimian thought. All three approaches contest the theoretical image of Durkheim’s social order, in other words, the individual subject to external constraints. Rather, all three pivot on a liberal and progressive line of thought with Durkheim, sustaining the voluntary dimension of action.